Quality Of Life In Patients With Chronic Dermatophytosis - Ajitesh Prakash Varshney; Pratik Gahalaut; Pavan Kumar Pardal; Nitin Mishra; Madhur Kant Rastogi; Manisha Thapa (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: The term “chronic dermatophytosis” can be described as patients who have suffered tinea infections for more than 6 months, with or without recurrence. Since last few years we are facing an onslaught of chronic and recurrent dermatophytosis. These infections are increasingly becoming debilitating with severe symptoms like itching and increasingly showing lack of response to traditional treatment, hence it has become utmost important to assess impact of dermatophytosis today on quality of life of patients.